2018
DOI: 10.4102/phcfm.v10i1.1773
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cervical abnormalities detected by visual inspection with acetic acid in Swaziland, 2011–2014: A retrospective study

Abstract: BackgroundCervical cancer is the fourth most common cancer worldwide among women, with the number of new cases increasing from 493 243 in 2002 to 527 000 in 2012. These numbers are likely to be underestimated because given the lack of registration resources, cervical cancer deaths are usually under-reported in low-income countries.AimTo describe the distribution of and trends in visual inspection with acetic acid (VIA) to detected cervical abnormalities in Swaziland by reviewing records of VIA examinations per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
(20 reference statements)
0
10
1
Order By: Relevance
“…25 Since one of the crucial points of the screening tests is their cost-effectiveness, some studies tend to recommend the VIA test as the best option. [10][11][12] However, the results from the present study show that it has too high a number of false positives (84.2%) with a very low PPV and, especially in a "screen-and-treat" approach, it may lead to overtreatment and excessive use of further examinations. Furthermore, the higher the number of women referred for extra examinations, the fewer the resources available in case of need.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…25 Since one of the crucial points of the screening tests is their cost-effectiveness, some studies tend to recommend the VIA test as the best option. [10][11][12] However, the results from the present study show that it has too high a number of false positives (84.2%) with a very low PPV and, especially in a "screen-and-treat" approach, it may lead to overtreatment and excessive use of further examinations. Furthermore, the higher the number of women referred for extra examinations, the fewer the resources available in case of need.…”
Section: Discussioncontrasting
confidence: 64%
“…[7][8][9] However, the VIA test did not show a high accuracy and some studies recommend it only because of its easy application in a low-resource setting. [10][11][12] whereas most of the studies propose a combination of tests. [13][14][15][16][17] The aim of the present study was to evaluate the efficacy and usefulness of the VIA test as well as of the VIA test combined with other screening techniques, such as the cervical smear, in Uganda in order to find possible solutions that may be used in a low-resource setting.…”
Section: Introductionmentioning
confidence: 99%
“…This study is the first to report on the implementation of smartphone-based telemedicine and AI in CaCx screening in Uganda. Studies from Tanzania [ 34 , 40 , 42 ], Madagascar [ 39 , 43 , 49 ], Eswatini [ 44 , 45 ], Botswana [ 35 , 77 ], Ghana [ 36 ], and Kenya [ 55 ] have used smartphone-based cervicography and have reported similar results as ours, including the ease of learning and adoption of smartphone-based telemedicine setups by CaCx screening staff, good-quality captured images that allow correct assessment by remote experts, and enhancement of VIA accuracy and clinical data management by such digital tools. Other studies from India [ 38 ] and Costa Rica [ 46 ] have attempted to develop AI models for analysis of cervical images, although clinical deployment has not been fully realized.…”
Section: Discussionmentioning
confidence: 99%
“…The long time service of cervical screening at family guidances prevents the pre-cancerous lesion from progression to suspicious for cancer. Studies in Swaziland, Cameroon, and Jakarta, Indonesia, showed VIA-positive rates of 15%, 3.33%, and 4.7%, respectively [10,11,12]. Though most are similar, the difference might be because of the skill difference of the care providers, and type of screening used.…”
Section: Plos Onementioning
confidence: 99%
“…A study in Uganda showed that 99% of women had heard about cervical cancer and 63% believed that family planning was a cause of cervical cancer as well as 85% recognizing inter-menstrual bleeding as a symptom of cervical cancer [9]. Other studies have also revealed the burden and public health importance of cervical cancer in LMICs [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%